Servant Leadership and Personality as Predictors of Work Productivity: The Mediating Role of Work Motivation - Iswanto, Heri; Entang, Muhamad; Yusnita, Nancy (Universitas Pakuan, 2024)
This study examines the effect of servant leadership and personality on employee work productivity, with work motivation as a mediating variable, among production employees of PT Restu Ibu Pusaka, Indonesia. The research was conducted in response to the declining productivity trends observed in the domestic body manufacturing industry, which faces both external market competition and internal workforce challenges. Using a quantitative associative approach, the study involved a sample of 134 employees selected from a population of 201 through the Slovin formula. Data were collected using structured questionnaires and analyzed using path analysis to determine direct and indirect relationships among variables. The results indicate that both servant leadership and personality have a positive and significant direct effect on work motivation and productivity. Additionally, work motivation itself has a significant direct influence on employee productivity, while also acting as a mediating factor that strengthens the indirect effects of servant leadership and personality on productivity. These findings demonstrate that leaders who prioritize empathy, wisdom, and service-oriented behavior can enhance motivation and performance by aligning organizational goals with employee well-being. Furthermore, employees with strong personality traits—such as conscientiousness, emotional stability, and openness—tend to exhibit higher motivation and productivity levels. The study underscores the importance of integrating servant leadership values and positive personality development within industrial organizations to sustain productivity and employee engagement.